2006
DOI: 10.1159/000097794
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of a Dutch DFNA9 Family with a Novel <i>COCH</i> Mutation, G87W

Abstract: The present study aims to report audiological and vestibular characteristics of a Dutch DFNA9 family with a novel mutation, G87W, in the LCCL domain of COCH. From the family with the novel G87W COCH mutation audiometric data were collected and analyzed longitudinally. Results were compared with those obtained in previously identified P51S COCH mutation carriers (n = 74) and with those obtained in G88E mutation carriers. Special attention was also given to a comparison of age-related features, such as progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
1
12
1
Order By: Relevance
“…We performed a comprehensive review and analysis of previously collected and reported clinical information on individuals and families with all 21 currently known COCH mutations (14 in the LCCL domain and seven in the vWFA domains), in addition to molecular characteristics of mutant cochlins from our new findings in this study and from past reports [Robertson et al., , ; de Kok et al., ; Fransen and Van Camp, ; Fransen et al., ; Kamarinos et al., ; Grabski et al., ; Usami et al., ; Nagy et al., ; Kemperman et al., ; Street et al., ; Collin et al., ; Pauw et al., , ; Yuan et al., ; Hildebrand et al., ; Baek et al., ; Hildebrand et al., ; Yao et al., ; Faletra et al., ; Cho et al.,) ; Dodson et al., ; Chen et al., ; Choi et al., ; Gallant et al., ; Gao et al., ]. These results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a comprehensive review and analysis of previously collected and reported clinical information on individuals and families with all 21 currently known COCH mutations (14 in the LCCL domain and seven in the vWFA domains), in addition to molecular characteristics of mutant cochlins from our new findings in this study and from past reports [Robertson et al., , ; de Kok et al., ; Fransen and Van Camp, ; Fransen et al., ; Kamarinos et al., ; Grabski et al., ; Usami et al., ; Nagy et al., ; Kemperman et al., ; Street et al., ; Collin et al., ; Pauw et al., , ; Yuan et al., ; Hildebrand et al., ; Baek et al., ; Hildebrand et al., ; Yao et al., ; Faletra et al., ; Cho et al.,) ; Dodson et al., ; Chen et al., ; Choi et al., ; Gallant et al., ; Gao et al., ]. These results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in COCH are causative of autosomal‐dominant nonsyndromic hearing loss, DFNA9, which has a late onset (ranging from 2 nd to 7 th decade of life) and progressive presentation, with variable degrees of vestibular malfunction such as dizziness, vertigo, and instability in the dark. To date, 21 COCH mutations (19 missense and two in‐frame deletions) have been reported throughout the world [Robertson et al., ; de Kok et al., ; Kamarinos et al., ; Usami et al., ; Nagy et al., ; Street et al., ; Collin et al., ; Pauw et al., , ; Yuan et al., ; Hildebrand et al., ; Faletra et al., ; Cho et al., ; Dodson et al., ; Chen et al., ; Choi et al., ; Gallant et al., ; Gao et al., ]. The true worldwide incidence of COCH mutations is not known, as systematic genetic screening for this and other genes resulting in late‐onset disorders is typically not performed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with other DFNA9/ COCH mutations vestibular failure can be less prominent. It is not invariably penetrant and/or occurs at a more advanced age [Kemperman et al, 2005; Pauw et al, 2007a].…”
Section: To the Editormentioning
confidence: 99%
“…Complete vestibular areflexia was present in many of the P51S COCH mutation carriers [Bischoff et al, 2005], but in far fewer G88E , G87W [Pauw et al, 2007a] and I109T [Pauw et al, 2007b] mutation carriers, in whom it occurred at a later age.…”
Section: Discussionmentioning
confidence: 96%